Análisis del cyberbullying y su afectación en las relaciones interpersonales de los estudiantes del grado séptimo de una institución educativa en Riohacha, La Guajira. (2021)
This research study is located in the educational field and cyber bullying. The objective is to analyze how bullying through social networks influences the interpersonal relationships of students. The theoretical supports are focused on the bibliographic study with illustrations that will be mentioned in the course of the investigation. The methods and techniques that were used in the student and professional population are made up of (1) psychologist to whom the interview technique was applied and (34) 701 grade students, whose ages range between 13 and 14 years old, To whom, after the authorization granted by their parents through informed consent, the battery of the Victimization Scale through the Mobile Phone and the Internet -CYBVIC- was applied the test was constructed by Buelga et al. (2012b) based on the “Peer Victimization Scale” by Cava et al.